Standar Akuntasi Keuangan Entitas Tanpa Akuntabilitas Publik (SAK ETAP) - Budiandru, Budiandru; Isfa, Shabrina Saufani (Agregat: Jurnal Ekonomi dan Bisnis, 2018)
This study aims to analyze the application of SAK ETAP on the presentation of financial statements CV SK. CV SK is a medium-sized businesses engaged in catering services and Wedding Organizer. The method used in this research is descriptive qualitative analysis. The results of the study based on Balance Sheet and Income Statement for 2012-2016, show that the company has not presented cash flow statement, and notes to financial statements (CALK) and inconsistency in the presentation of some post on Balance Sheet not disclosed in CALK. This research suggests that companies develop other components of financial statements and disclose the company's accounting policies in CALK.